RETHINKING WELL-BEING INPUT FOR CREATIVE PERSON - Umukoro, Jones E.; Egwakhe, Johnson A.; Falana, Ranti B. (Journal of Business And Entrepreneurship, 2021)
The strength of an organisation lies predominantly in her personnel as the creative person. However, limited studies on well-being input exist in developing countries. Also, the scope and methodological gap in a previous study conducted on flexible well-being and smart-head necessitated this study. Thus, the paper determined the effect and sensitivity relationship of redefined well-being dimensions on creative person. A cross-sectional survey research design was used while a validated questionnaire was distributed and 532 retrieved from academic staff ranked as Senior Lecturer, Associate Professor and Professor. The multi-stage random sampling technique was applied to eight selected private universities in South-West Nigeria. Findings from multiple regression analysis conducted revealed that redefined well-being had a combined positive significant effect on creative person [(Adj. R2 = 0.331 (F (6, 525) = 44.877, p<0.05)] and the artificial neural network analysis showed technological work environment as the best individual predictor. The paper strengthens the Person Environment (P-E) Fit Theory assumptions and the position to consistently redefine well-being input as a maxim to stimulate academics’ creativity for a novel knowledge-based economy, patent, and ranking.